2(7-3) fractional factorial optimization of polybenzimidazole based membrane electrode assemblies for H-2/O-2 fuel cells - Kannan, Ramaiyan; Islam, Md. Nazrul; Rathod, D.; Vijay, M.; Kharul, Ulhas K.; Ghosh, P. C.; Vijayamohanan, K. (Journal of Applied Electrochemistry, 2008)
We describe the usefulness of a statistical fractional factorial design to obtain consistent and reproducible behavior of a membrane-electrode-assembly (MEA) based on a phosphoric acid (PA) doped polybenzimidazole (PBI) membrane, which allows a H-2/O-2 fuel cell to operate above 150 degrees C. Different parameters involved during the MEA fabrication including the catalyst loading, amount of binder, processing conditions like temperature and compaction load and also the amount of carbon in the gas diffusion layers (GDL) have been systematically varied according to a 2(7-3) fractional factorial design and the data thus obtained have been analyzed using Yates's algorithm. The mean effects estimated in this way suggest the crucial role played by carbon loading in the gas diffusion layer, hot compaction temperature and the binder to catalyst ratio in the catalyst layer for enabling continuous performance. These statistically designed electrodes provide a maximum current density and power density of 1,800 mA cm(-2) and 280 mW cm(-2), respectively, at 160 degrees C using hydrogen and oxygen under ambient pressure.
Keywords: Carbon loading; Fractional factorial optimization; MEA; PBI; PEMFC

Polymer electrolyte fuel cells using nafion-based composite membranes with functionalized carbon nanotubes - Kannan, Ramaiyan; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Angewandte Chemie-International Edition, 2008)
Keywords: fuel cells; membranes; nanotubes; Polymers; proton transport

Synthesis of platinum Y-junction nanostructures using hierarchically designed alumina templates and their enhanced electrocatalytic activity for fuel-cell applications - Mahima, Subhramanyam; Kannan, Ramaiyan; Komath, Indulekha; Aslam, Mohammed; Pillai, Vijayarnohanan K. (Chemistry of Materials, 2008)

Design of an "allsolid-state'' supercapacitor based on phosphoric acid doped polybenzimidazole (PBI) electrolyte - Rathod, Dhanraj; Vijay, Meenu; Islam, Md. Nazrul; Kannan, Ramaiyan; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan (Journal of Applied Electrochemistry, 2009)
The effectiveness of phosphoric acid doped polybenzimidazole as a polymer electrolyte membrane to fabricate an all solid-state super capacitor has been explored using hydrous RuO(2)/carbon composite electrodes (20 wt.%) of surface area 250 m(2) g(-1) with many intrinsic advantages. The electrochemical evaluation of these super capacitors through cyclic voltammetry, charge/discharge and impedance measurements demonstrate the utility of this type of thin, compact and flexible supercapacitor capable of functioning at 150 degrees C to yield a maximum capacitance of about 290 F g(-1) along with a life of more than 1,000 cycles. A power density of 300 W kg(-1) and energy density of 10 Wh kg(-1) have been accomplished although the equivalent series resistance (ESR) of about 3.7 Omega needs to be reduced further for high rated applications.
Keywords: Electrochemical characterization; Electrochemical supercapacitor; Energy storage device; PBI electrolyte; RuO(2)/carbon composite

Domain size manipulation of perflouorinated polymer electrolytes by sulfonic acid-functionalized MWCNTs to enhance fuel cell performance - Kannan, Ramaiyan; Parthasarathy, Meera; Maraveedu, Sreekuttan U.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Langmuir, 2009)
The application of sulfonic acid-functionalized multiwalled (s-MWNT) carbon nanotubes to manipulate the hydrophilic domain size of Nafion membranes is explored here as an option for tuning the proton conductivity of polymer electrolyte membranes for hydrogen-oxygen fuel cells. The electrochemical impedance experiments provide preliminary evidence of increased proton conductivity, while small-angle X-ray scattering measurements line. out enhanced ionic cluster domain size in these composite membranes as the central reason for higher conductivity (70 angstrom for the optimum composite membrane vs 50 angstrom for Nafion 115) values. Scanning electrochemical microscopy indicates synergistic interaction between the sulfonic acid functional groups present in the Nation membrane and those on the nanotube surface. More interestingly, the nanotube-tailored Nafion membranes ameliorate the performance of fuel cells as confirmed by measurements at a sin le-cell level, which reveal a maximum power density of 380 mW cm(-2), higher than those of Nafion 115 (250 mW cm(-2)) and recast Nafion (230 mW cm-2) membranes. Thus, in addition to providing an elegant means of controlling the ionic cluster size, the strategic approach of using CNT both as an anchoring backbone for -SO(3)H groups to enrich proton conductivity and as a blending agent to improve the mechanical characteristics of the Nafion phase might be helpful in alleviating many critical problems associated with the use of commercial Nafion membranes.

Artificially designed membranes using phosphonated multiwall carbon nanotube-polybenzimidazole composites for polymer electrolyte fuel cells - Kannan, Ramaiyan; Aher, Pradnya P.; Palaniselvam, Thangavelu; Kurungot, Sreekumar; Kharul, Ulhas K.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry Letters, 2010)
The ability of phosphonated carbon nanotubes to offer an unprecedented approach to tune both proton-conductivity and mechanical stability of hybrid polymer electrolytes based on the polybenzimidazole membrane is demonstrated for fuel cell applications. The covalent attachment between the amino group of the 2-aminoethylphosphonic acid precursor and CNTs has been confirmed by NMR and IR experiments, while EDAX analysis indicates that one out of every 20 carbon atoms is in the CNT is functionalized. Proton conductivity of the composite membrane shows a remarkable 50% improvement in performance while a maximum power density of 780 and 600 mW cm(-2) is obtained for the composite and pristine membranes, respectively. Finally, the ultimate strength determined for the composite and pristine membranes is 100 and 65 MPa, respectively, demonstrating the superiority of the composite. This study opens up a new strategy to systematically tune the properties of polymer electrolytes for special applications by using appropriately functionalized CNTS.

Bio-inspired catalyst compositions for enhanced oxygen reduction using nanostructured Pt electrocatalysts in polymer electrolyte fuel cells - Parthasarathy, Meera; Kannan, Ramaiyan; Sreekumar, Kurungot; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2010)
Composites of Nafion with a class of bio-molecules viz., plant hormones, are explored as potential polymer electrolytes for improving the proton transport inside the catalyst layer of a H(2)/O(2) fuel cell. Specifically, four nitrogenous plant hormones, two each from the class of auxins and cytokinins have been investigated, following preliminary characterization of the composite dispersions and membranes. Interestingly, the use of indole-3-acetic acid (an auxin) in the catalyst layer reveals a 30% enhancement in Pt catalyst utilization and improved fuel cell performance by 150 mW cm(-2). The effect of these bio-molecules on the kinetic and mass transport parameters has been analyzed systematically using a combination of electrochemical and spectroscopic techniques.

Enhanced electrocatalytic performance of functionalized carbon nanotube electrodes for oxygen reduction in proton exchange membrane fuel cells - Kannan, Ramaiyan; Bipinlal, Unni; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Physical Chemistry Chemical Physics, 2011)
Although nitrogen doped CNTs (N-CNTs) are considered as a promising alternative to platinized carbon for the oxygen reduction reaction (ORR) in polymer electrolyte membrane fuel cells (PEMFCs), the origin of the enhanced ORR activity with N-CNTs is not clear at present. Among several plausible reasons, the exposure of edge plane and creation of impurity band/surface states near the Fermi level are considered as major causes behind the catalytic activity. However, CNTs without nitrogen doping are not known to catalyze the ORR. In this work, we study the ORR activity of functionalized carbon nanotubes with different functional groups, such as sulfonic acid and phosphonic acid, in order to understand the role of surface functionalities in catalyzing the reaction. Functionalized CNTs show significantly enhanced activity towards the ORR, while CNTs without such surface functional groups do not reveal any such special ORR activity. Linear sweep voltammetry experiments with different rotation rates show diffusion controlled limiting current values for functionalized CNTs, and the `n' values derived from Koutecky-Levich plots are 3.3 and 1.7 for S-MWCNTs and P-MWCNTs, respectively. This work demonstrates the ORR activity of functionalized MWCNTs, which opens up new strategies for electrocatalyst design in PEMFCs.

Facile construction of non-precious iron nitride-doped carbon nanofibers as cathode electrocatalysts for proton exchange membrane fuel cells - Palaniselvam, Thangavelu; Kannan, Ramaiyan; Kurungot, Sreekumar (Chemical Communications, 2011)
We demonstrate a facile construction of iron nitride-doped carbon nanofiber by effectively utilizing the existing slit pores and rough edges along the inner wall of the substrate as originated by virtue of its cup-stack structure for effectively increasing the number of active sites and consequently the oxygen reduction activity.

Improved performance of phosphonated carbon nanotube-polybenzimidazole composite membranes in proton exchange membrane fuel cells - Kannan, Ramaiyan; Kagalwala, Husain N.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2011)
Development of thermally stable polymer electrolyte membranes with higher proton conductivity as well as mechanical stability is a key challenge in commercializing PEM fuel cells operating above 100 degrees C. Polybenzimidazole membranes are one of the promising candidates in this category although with limited mechanical stability and moderate proton conductivity. Here the incorporation of functionalized MWCNT is shown to increase both these key parameters of the polybenzimidazole membranes. Further, formation of a domain like structure after the incorporation of phosphonated MWCNTs (P-MWCNTs) in phosphoric acid doped polybenzimidazole membranes is demonstrated. The enhanced performance has been attributed to the formation of proton conducting networks that formed along the sidewalls of P-MWCNTs with a domain size of 17 nm as estimated from the small angle X-ray scattering measurements. Membrane electrode assembly (MEA) impedance measurements further reveal that the activation energy of oxygen reduction reaction (ORR) reduced for the composite membranes with enhanced proton conductivity. In addition, the mechanical strength measurements reveal a significant improvement in the yield strength and ultimate strength. Also, the mechanical strength of the composite membrane has been increased significantly as indicated by the improvement in the ultimate strength from 65 MPa to 100 MPa for the pristine and composite membranes, respectively. The optimum loading of P-MWCNTs is found to be 1% as inferred from the polarization measurements carried out using pure hydrogen and oxygen. Thus, this study provides a unique opportunity to tune the properties of polymer electrolytes to prepare application oriented hybrid membranes using CNTs with tailor-made functional groups.

Charge transport in functionalized multi-wall carbon nanotube-Nafion composite - Sangeeth, C. S. Suchand; Kannan, Ramaiyan; Pillai, Vijayamohanan K.; Menon, Reghu (Journal of Applied Physics, 2012)
The charge transport in sulfonated multi-wall carbon nanotube (sMWNT)-Nafion composite is reported. The scanning electron microscope images of the composite, at 1 and 10 wt % of sMWNT, show that the nanotubes are well dispersed in polymer matrix, with conductivity values of 0.005 and 3.2 S/cm, respectively; and the percolation threshold is nearly 0.42 wt. %. The exponent (similar to 0.25) of the temperature dependence of conductivity in both samples indicates Mott's variable range hopping (VRH) transport. The conductance in 1 wt. % sample increases by three orders of magnitude at high electric-fields, consistent with VRH model. The negative magnetoresistance in 10 wt. % sample is attributed to the forward interference scattering mechanism in VRH transport. The ac conductance in 1 wt. % sample is expressed by sigma(omega) proportional to omega(s), and the temperature dependence of s follows the correlated barrier hopping model. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4749264]

Porous Co3O4 nanorods as superior electrode material for supercapacitors and rechargeable Li-ion batteries - Vijayanand, S.; Kannan, Ramaiyan; Potdar, H. S.; Pillai, V. K.; Joy, Pattayil Alias (Journal of Applied Electrochemistry, 2013)
Porous aggregated nanorods of Co3O4 with a surface area of similar to 100 m(2) g(-1) synthesized without using any templates or surfactants give very high specific capacitance of similar to 780 F g(-1) when used as electrode in a faradaic supercapacitor, with a cycle life of more than 1,000 cycles. Further, in Li-ion batteries when used as an anode, the Co3O4 nanorods achieved a capacity of 1155 mA h g(-1) in the first cycle and upon further cycling it is stabilized at 820 mA h g(-1) for more than 25 cycles. Detailed characterization indicated the stability of the material and the improved performance is attributed to the shorter Li-insertion/desertion pathways offered by the highly porous nanostructures. The environmentally benign and easily scalable method of synthesis of the porous Co3O4 nanorods coupled with the superior electrode characteristics in supercapacitors and Li-ion batteries provide efficient energy storage capabilities with promising applications.
Keywords: Cobalt oxide; Electrode materials; Li-ion battery; Porous nanostructures; supercapacitor